An unusual intraosseous calcaneal lipoma: case report - Alkan, Ender; Erdoğan, Hasan; Kara, Turgay (The European Research Journal, 2018)
Intraosseous lipoma, a rare primary benign tumor of the skeleton, is most commonly found in the calcaneus. It may contain homogenous fat, but it may also contain necrosis, calcification, or ossification. It usually does not show contrast enhancement, but there is an interface enhancement between the outer fat plan and the inner fluid part. Herein, we present an unusual 22-year-old male case of calcaneal intraosseous lipoma with contrast enhancement in the fatty component. The lesion was totally curetted and replaced with bone graft. The pathological diagnosis was reported as an intraosseous lipoma. The correct diagnosis of an atypical calcaneal intraosseous lipoma is very important to prevent an unnecessary biopsy and treatment.